2020
DOI: 10.12688/gatesopenres.12961.2
|View full text |Cite
|
Sign up to set email alerts
|

Abortion knowledge and experiences among young women and men in Accra, Ghana

Abstract: Background: Despite the presence of legal abortion services in Ghana, unsafe abortion remains common, particularly among young women. Little is understood about what young people know about safe and legal abortion, and if and how they are utilizing it. Methods: To characterize abortion use and address gaps in safe access, from September-December 2013, we conducted a cross-sectional survey with 100 men and 250 women aged 18-24 in Accra, Ghana. Participants were asked about abortion experiences, including prior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 8 publications
4
11
0
Order By: Relevance
“…33 The findings of this study further revealed that women in urban areas were less likely to engage in unsafe abortion methods compared to their rural counterparts. Similar results were found by earlier studies in Ghana 20 25 and Mozambique. 35 The possible explanation to this is the lack of access to safe abortion services among women in the rural areas.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…33 The findings of this study further revealed that women in urban areas were less likely to engage in unsafe abortion methods compared to their rural counterparts. Similar results were found by earlier studies in Ghana 20 25 and Mozambique. 35 The possible explanation to this is the lack of access to safe abortion services among women in the rural areas.…”
Section: Discussionsupporting
confidence: 92%
“…This means the prevalence of unsafe abortions have doubled over the decade among women in Ghana. Similar findings were of high rate of abortion incidence were found by other studies recently in Ghana 20 25 , Ethiopia 49 and Nepal. 50…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations